Digital Boundaries and Imaginaries of Khasi Ethnic Identity in Social Media - Rajani K. Chhetri; Fr. (Dr) George Plathottam (CV. Literasi Indonesia, 2021)
Identity is an integral aspect of human cognition and a composite of varied elements and subjectivities; it is fluidic and contextual. Identity discourses have dominated the socio-cultural and political milieu of Northeast India. A range of scholarship emanating from both within the Northeast region and outside has explored several identity dimensions. As the social media site Facebook allows for the formation of different kinds of interactional groups, this study explored a closed private Facebook group of twenty-five thousand members belonging exclusively to the Khasi ethnic community to understand the phenomenon of ascribing Khasi social identity among members in the online group. The study adopts Tajfel’s Social Identity framework and engages in a netnographic study on an online group. The study’s findings reveal a range of key symbolic manifestations in the co- constructions of Khasi identity in the online space. The study also discovers unique possibilities and affordances proliferated by social media in building collectivities, strengthening ethnic ties, and belongingness in the online space.